Chasing the breath of life: Lung transplantation from the viewpoint of a patient. Issue 4 (17th January 2023) - Herman, Stewart W.
Abstract: Have you ever wondered about what an organ transplant involves? This article provides a window into the experience of one patient receiving new lungs. My aim is to provide signposts for anyone else who stumbles into lung disease and then struggles for recovery from this mortal threat. Call it a "memoir of resilience"—one person's effort to bend without breaking in response to a series of medical challenges. I hope my experience might help other people with compromised lungs gain a glimmer of what to expect and provide a framework for families, friends, pastors, and others to understand what is happening from outside.